2020
DOI: 10.1073/pnas.2003991117
|View full text |Cite
|
Sign up to set email alerts
|

Efficient photoactivatable Dre recombinase for cell type-specific spatiotemporal control of genome engineering in the mouse

Abstract: Precise genetic engineering in specific cell types within an intact organism is intriguing yet challenging, especially in a spatiotemporal manner without the interference caused by chemical inducers. Here we engineered a photoactivatable Dre recombinase based on the identification of an optimal split site and demonstrated that it efficiently regulated transgene expression in mouse tissues spatiotemporally upon blue light illumination. Moreover, through a double-floxed inverted open reading frame strategy, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Therefore, 48 h of pulse illumination (1 min pulse every 5 min) was approximately 8 h of continuous illumination which was shorter than a previous study which used 16 h of continuous illumination. [ 12 ] In addition, users can shorten the illumination time via increasing the illumination strength, extending the illumination pulse, or designing new illumination strategies by using an optical fiber [ 15 , 23 , 24 ] or two‐photon. [ 13 ] In summary, the data above demonstrated that the recombinase activity was activated efficiently and dramatically in various tissues upon blue light induction in ePA‐Cre: Ai14 mice without obvious background activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 48 h of pulse illumination (1 min pulse every 5 min) was approximately 8 h of continuous illumination which was shorter than a previous study which used 16 h of continuous illumination. [ 12 ] In addition, users can shorten the illumination time via increasing the illumination strength, extending the illumination pulse, or designing new illumination strategies by using an optical fiber [ 15 , 23 , 24 ] or two‐photon. [ 13 ] In summary, the data above demonstrated that the recombinase activity was activated efficiently and dramatically in various tissues upon blue light induction in ePA‐Cre: Ai14 mice without obvious background activity.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several elegant photoactivatable recombinases have been developed mainly based on the CRY2‐CIB1 [ 10 ] and Magnets system, [ 28 ] such as PA‐Cre, PA‐Flp, and PA‐Dre, offering promising approaches for high‐resolution spatiotemporal transgenesis. [ 10 , 11 , 12 , 23 , 24 ] In this study, we optimized the PA‐Cre2.0 system leading to ePA‐Cre, which exhibited enhanced efficiency and reduced leakage compared with other tested PA‐Cre systems. A transgenic mouse strain containing the ePA‐Cre system was generated, and the Cre activity was stringently responsive to blue light illumination in multiple mouse tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Further controls showed that antibody binding does not occur in the absence of BphP1-mCherry-His 6 ( Figure S2B,C,E,F ) and that neither far-red nor red light affects the particle morphology ( Figure S2G,H ). The BphP1/QPAS1 system has previously been used to control gene expression and protein activity in vivo [ 5 , 16 , 72 ] but again this is the first study to demonstrate the functionality of BphP1/QPAS1 on the surface of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo feasibility was elegantly demonstrated in a rodent model to drive Cav3.1 silencing in the medial septum neurons to increase object-exploration behaviors [108]. Recently, photoactivatable Dre recombinases, named as PA-Dre and iDreV, were independently developed by two groups by using Magnet or VVD-based optical dimerizers for light-inducible restoration of Dre activity [109,110]. Both tools showed light-dependent DNA recombination events in rodent models.…”
Section: Trends In Geneticsmentioning
confidence: 99%